Children older than five years do not approve of wasting food: An experimental study on attitudes towards food wasting behavior in children and adults. (October 2020) - Sorokowska, Agnieszka; Marczak, Michalina; Misiak, Michał; Stefańczyk, Michał Mikołaj; Sorokowski, Piotr
Abstract: Food loss and food waste extensively contribute to environmental degradation. Children waste large quantities of food and more research is required to better understand this problem and consequently to reduce food waste in the youngest generation. Here, we examined affective and behavioral components of attitudes towards food-wasting in a group of 670 children and 123 adults, aged 3–28. The participants viewed food wasting and food saving in a video, and we tested whether age affected the moral-emotional and behavioral reactions to a food wasting vs. food saving person. The attitude towards the food wasting protagonist (operationalized as "liking" indicated on a pictorial scale) was significantly more negative than that towards the food saving protagonist in all age groups except for the three- to five-year old children. Behavioral attitude towards the video protagonists was defined as a willingness to share some goods with a food wasting vs. a food saving person, and in our study, food wasting protagonist received equal amount or less resources distributed by the participants. Additionally, our data suggest that food wasting preferentially affected food sharing in adults, but not in children, as food was shared with the food wasting protagonist in significantly smaller quantities than pens by the oldest age group. In summary, we show that even preschoolers disapprove of food wasting behavior, but only in 6–7 year old children this attitude begins to become well established; it consolidates at the age of 8–9 and starts to include a behavioral component at the age of 10–12. We suggest that pro-environmental interventions targeting food waste reduction in children should start at middle childhood and focus on behavior. Highlights: Children waste large quantities of food which contributes to environmental degradation. We experimentally examined attitudes towards food-wasting in children and adults. Emotional attitude towards food wasting was negative starting from 6 years of age. Food-wasting negatively affected participants' behavioral reactions (sharing patterns). Interventions targeting waste reduction should start at the age of 6 years and focus on behavior.